Coorrelation Of Nutritional Status In Toddlers With The Stunting Incident At The Panyabungan Jae Puskesmas, Panyabungan City District Mandailing Regency Year 2022 - Helmi wardah Nasution (Institute of Computer Science (IOCS), 2022)
Stunting is one of the problems that hinders human development globally. Stunting is a picture of nutritional status that is chronic and is the impact of long-lasting conditions such as economic status, poor parenting and often suffer from recurring diseases. The prevalence of stunting in Mandailing Natal Regency in 2020 was 42.13%, while at the Panyabungan Jae Health Center it was 3.4%. The purpose of this study was to analyze the relationship between nutritional status and the incidence of stunting in toddlers in the Panyabungan Jae Health Center, Mandailing Natal Health Center. This research is an analytic survey with a cross sectional approach. The study population was 82 mothers who had toddlers and samples were taken using the Random Sampling technique using the Slovin formula so that a sample of 45 toddlers was obtained. The research instrument used primary data (questionnaire) consisting of 20 questions. The independent variable in this study is nutritional status which includes education level, economic status, maternal age and parity. And the dependent variable in this study is the incidence of stunting. Collecting data using a nutrition report book, processing data by editing, coding, tabulating, then tested with the Chi-Squer test. The results of the study, most of the children under five as many as 20 people (44.4%) of respondents had adequate nutritional status. And all respondents experienced stunting. The results of the Chi-Square test obtained p-value 0.025 <0.05 so that Ho is rejected and Ha is accepted. In this study, there was a relationship between the nutritional status of children under five and the incidence of stunting in the Panyabungan Jae Health Center Work Area, Panyabungan District, Mandailing Natal Regency. It is hoped that the cooperation of health workers, cadres and parents to fulfill balanced nutrition for toddlers to avoid stunting.